Pop painting : inspiration and techniques from the pop surrealism art phenomenon - D'Errico, Camilla (Berkeley : Watson-Guptill Publications, 2016)
"A unique behind-the-scenes guide to the painting process of one of the most popular artists working in the growing, underground art scene of Pop Surrealism. Painting superstar Camilla d'Errico opens up her studio and offers readers an insider scoop on the tools, techniques, and inspirations she draws from to create stunningly beautiful, otherworldly works of art. Pop Surrealism, with its unique blend of high art and popular culture, has been a growing force in the art world for years. Artists working in Pop Surrealism use elements of manga, cartoons, movies, and more to produce paintings that have been displayed in galleries and purchased by collectors around the globe. In addition to her work in manga and as the author of the best-selling Pop Manga, d'Errico is also one of the Pop Surrealism movement's biggest names. From high-end art galleries to comic book conventions, d'Errico's works draw legions of fans, collectors, and admirers. With Pop Painting, fans and aspiring painters get an up-close look at the step-by-step processes she employs to transform oil and acrylic paints into unforgettable images of her ethereal and beautiful characters. This one-of-a-kind look at a painter at the top of her field reveals all the materials and methods readers need to join the ranks of the Pop Surrealism movement"--
Foreword / Greg "Craola" Simkins -- Introduction -- part 1. Creating pop surrealism -- 1. Pop surrealism : what is it? -- The evolution of pop surrealism -- Pop surrealism : be inspired! -- 2. Originality, inspiration, and intuition -- What inspires me -- Finding inspiration -- Using intuition : go with your gut! -- Choosing colors intuitively -- Choosing titles intuitively -- Becoming a better artist -- 3. Tools of the trade -- Paint -- Drawing tools -- Brushes -- Painting surfaces -- Easels -- Other helpful tools -- Selecting your tools -- 4. The artist's studio -- Setup -- Organization -- Safety -- Creative space : what is needed -- Outside studio vs. home studio -- 5. Sketching, studying, or just doing it? -- Sketching : trials and errors -- Practice first -- Do it! -- 6. Composition -- Juxtaposition -- What to do if you run out of room -- What to do when something is missing -- 7. Pushing boundaries -- Paint with your gut, not your head -- Dealing with blocks and dry spells -- don't let failure get to your heart : move on! -- 8. Evoking emotions -- Tapping into emotions -- Your emotions while painting -- Getting in the mood -- Coloring emotion -- Subject matter and emotion -- Expressing your emotional meaning -- The power of emotions -- 9. Blending -- Blending basics -- Blend, set, go! -- Light and shadows -- Depth : an in-depth look -- part 2. Painting pop surrealism -- Top ten questions -- Tips and tricks -- 10. Step-by-step examples -- Humans -- Eyes -- Lips -- Hair -- Skin -- Depth -- Animals -- Fur -- Wings -- Baby animals -- Rainbow tigers -- Melting effects -- Pools of color -- Melting rainbow -- Twisting reality -- Combining cuteness -- Tentacles -- Cartoons and caricatures -- Butterfly kisses -- 11. Black and white: paint drawing -- Surface preparation and underdrawing -- The paint drawing process -- How to paint straight lines -- How to paint over the canvas edges -- 12. Passion to profession -- My art evolves -- How I learned to love painting -- Finding my creative home in pop surrealism-- On being a professional artist -- Approaching galleries and getting started -- Presenting your portfolio -- Dealing with rejection -- Validate yourself.
Includes index.
Includes bibliographical references and index.
Keywords: D'Errico, Camilla -- Themes, motives; Painting -- Technique; Pop art -- Themes, motives